Who is afraid of ticks and tick-borne diseases? Results from a cross-sectional survey in Scandinavia - Daniel Slunge; Solveig Jore; Karen Angeliki Krogfelt; Martin Tugwell Jepsen; Anders Boman (BMC, 2019)
Abstract Background In Scandinavia, the distribution of ticks is expanding and tick-borne diseases constitute growing health risks. While the probability of getting a tick-borne disease after a tick bite is low, the health impacts can be large. This, as well as other characteristics of these diseases make tick-related risks difficult for laypeople to assess and perceived risk may differ substantially from actual risk. Understanding risk perceptions is important since it is the perceived risk, rather than actual risk, that determine behaviour and even more so for new and emerging risks. The aim of this study is to investigate knowledge and risk perceptions related to tick bites and the tick-borne diseases Lyme borreliosis (LB) and tick-borne encephalitis (TBE). By analysing risk perceptions and knowledge, the study helps inform the development of public health strategies in response to the increasing incidence of these diseases in Scandinavia. Methods Two thousand, six hundred sixty-eight respondents in Denmark, Norway and Sweden answered an online questionnaire with 48 questions, including 7 questions on risk perceptions and 9 knowledge questions. Chi-squared tests were used to analyse statistical differences between country sub-samples, gender and age groups. A multivariate regression model was used to analyse factors associated with risk perceptions. Results Risk perceptions were on average high in comparison with scientific estimates, with respondents grossly overrating the probability of contracting LB or TBE if bitten by a tick. Also, the average perceived seriousness of a single tick bite and of getting LB or TBE was high. Knowledge on the other hand was low, especially among men and the youngest age group (18-29 years). Higher levels of knowledge about tick-borne diseases were associated with lower perceived seriousness of tick bites and LB and higher perceived seriousness of TBE. Also, having been diagnosed with LB was negatively associated with the perceived seriousness of LB. Conclusions Our results indicate that informing about ticks and tick-borne diseases would be a relevant public health strategy as it could make risk perceptions better aligned with actual risk. Should the TBE virus spread further in Denmark and Norway, increasing knowledge about TBE vaccination would be especially important.